Adaptability of Broilers to Dietary Phosphorus Repletion and Depletion Programs - Cardinal , Katia Maria; Silva, Jessica Pereira; Pires, Paula Gabriela da Silva; Orso, Catiane; Gomes, Bruna Cristina Kuhn; Vilella, Lucas de Marques; Stefanello, Thais Bastos; Andretta, Ines; Ribeiro, Andrea Machado Leal (International Journal of Poultry Science, 2020)
Objective: This study was designed to evaluate the ability of broiler to adapt the diets with phosphorus (P) depletion and repletion. Materials and Methods: A total of160 broilers were housed in 20 pens. Two diets based on corn and soybean were formulated to pre-initial and initial phases: Control - formulated within nutritional recommendation; Reduced-without dicalcium phosphate -0.15% of available P. Treatments consisted of four P supply schemes: Normal P (NP)-control diet during entire trial; Depletion (DP)-Control diet in pre-initial and reduced level diet provided during the initial phase; Repletion (RP)-reduced diet during the pre-initial and control diet in initial phase and Reduced P (RL)-reduced diet during the pre-initial and initial phases. All broilers received control diet during grower phase. Body weight, feed intake and feed conversion were evaluated. Carcass yield and bone mineral contents were assessed at 21 and 28 days. Data were analyzed using ANOVA and Tukey test (p<0.05). Results: Broilers fed with RL diet showed impaired performance compared to NP treatment. Broilers fed with NP and RP diets presented higher weight gain and feed intake and similar tibia mineralization after 21 or 28 days. Conclusion: Although, practical application depends on further research, broilers fed phosphorus supplemented diet have the ability to recover body weight, weight gain and bone mineralization.